NUTRIENT CONTENT IMPROVEMENT OF TAPIOCA WASTE AND RICE BRAN AS INGREDIENTS TROUGH FERMENTATION USING Azospirillum sp. JG3 - Tati Febrianti; Oedjijono Oedjijono; Ning Iriyanti (Pusbindiklat - LIPI, 2017)
Azospirillum sp. JG3 is known to be able to grow in a mixture of tapioca waste and rice bran through fermentation. However, improved the nutrient content of tapioca waste and rice bran using Azospirillum sp. JG3 is not yet known. This research aimed to know the capability of Azospirillum sp. JG3 in improving thenutrient content of tapioca waste and rice bran mixture and incubation times needed to produce the highest nutrient mixture. The method used in the experiment was Completely Randomized Design (CRD). Treatments were incubation times i.e. 0, 3, 4, 5, 6, and 7 days, and each treatment was replicated three times. Azospirillum sp. JG3 is inoculated into a mixture of tapioca waste and rice bran. As results, Azospirillum sp. JG3 was able to improve the nutrient content of tapioca waste and rice bran in five days fermentation. A significant increase in protein content (29,15%) and a decrease in crude fiber (36,63%) were recognized when tapioca waste and rice bran are fermented with Azospirillumsp. JG3 compared to non-fermented one.